Kindling the fire: Fueling preservice science teachers' interest to teach in high‐needs schools. Issue 4 (2nd April 2019) - Kier, Meredith W.; Chen, Jason A.
Abstract: This study applies psychological models of interest and motivation (i.e., a model of interest‐development and self‐determination theory) to the experiences of six preservice science Noyce scholars who participated in a teacher preparation program. The National Science Foundation's Noyce grant aims to incentivize mathematics and science majors to teach in high‐needs school districts. Through this interview study, we sought to understand how Noyce scholars' pre‐existing interests and their experiences in the Noyce program interact to develop individual commitments to teach in high‐needs school settings. Case studies reveal that scholars had no prior experiences in high‐needs schools, abstract ideas about teachers, students, and resources in these contexts, and varying degrees of initial connectedness to teaching in high‐needs school settings. Scholars found that site visits to diverse high‐needs schools (i.e., rural and urban) triggered their interest to teach in similar contexts. Preservice science teachers' emerging interest and level of commitment to teaching in high‐needs schools following the teacher preparation program was dependent upon context‐specific mastery experiences and autonomy within their long‐term clinical field experience. This study offers implications for teacher educators who are recruiting and preparing students to teach in high‐needs school contexts.